Improving the postproduction quality of Rose cut flowers - Hassan, F.; Schmidt, G.; Dorogi, Zs. (International Journal of Horticultural Science, 2004)
In order to improve the post production quality of cut flowers of Rosa hybrida L. cv. Baroness, the effect of 8-hydroxyquinoline sulfate (8-HQS), silver thiosulfate (STS) and 1-methylcyclopropene ( I-MCP) were investigated. 8-HQS was used at 200 and 400 ppm with or without sucrose at 50 g LI. STS was used at 0.2, and 0.4 mM with or without sucrose at 50 g 1-I. l-MCP was used at 0.3, 0.5 and 0.7 g in-3 for 6h. The postproduction quality was improved as a result of using any chemical treatment comparing with untreated control. All the treatments of 8-HQS increased the vase life and minimized the percentage of weight loss of rose cut flowers compared to the control. The vase life was lorger when 8-HQS was combined with sucrose. The best treatment of 8-HQS was 400 ppm 8-HQS + 50 g 1-1 sucrose. STS treatment led to prolong the vase life and minimized the percentage of weight loss compared to the control. In addition, the effect was better when sucrose was added to STS. The treatment of STS at 0.4 mM + 50 g 1-1 sucrose was the best one. l -MCP treatment prolonged the vase life and lowered the percentage of weight loss at any level compared with untreated control. The best treatment in this concern was l -MCP at 0.5 g m-3 for 6h. The chlorophyll content (chl.a and chid)) of the leaves for the best treatment of each chemical was higher than the control. The treatment of STS at 0.4 mM + 50 g 1-1 sucrose gave the best results in this respect.